Ravasz László homiletikai elméletének és prédikációs gyakorlatának összevetése - Mária KUN (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Comparison of Homiletical Theory and Preaching Practice in the Work of László Ravasz